Sidewall functionalization of carbon nanotubes - Holzinger, Michael; Vostrowsky, Otto; Hirsch, Andreas; Hennrich, Frank; Kappes, Manfred; Weiss, Robert; Jellen, Frank (Angewandte Chemie International Edition, 2001)
The addition of nitrenes, nucleophilic carbenes, and radicals affords soluble, individual single-walled nanotubes (shown here is a carbene-functionalized adduct) by covalent sidewall functionalization. The characterization, a fundamental problem in nanotube chemistry, is simple to carry out.